Peran Serta Masyarakat Dalam Upaya Pemberantasan Tindak Pidana Korupsi Di Indonesia - Maria Febriana Seuk; Yohana A. C. Beto. Koten; Thomas Kemil Masi; Marsi Devid Setyawan Bani (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Corruption crimes have resulted in the destruction of the nation's economy. This journal aims to examine the role of the community in efforts to eradicate corruption and how the government's efforts to optimize the prevention and eradication of criminal acts of corruption in Indonesia. The issue of public awareness or public awareness and concern for the dangers of corruption and the issue of community empowerment is a very important part of efforts to eradicate corruption. One way to increase public awareness is to carry out a campaign about the dangers of corruption. Socialization and dissemination in the public space regarding what corruption is, the effects of corruption and how to fight corruption must be intensified. The campaign can be carried out using mass media (both printed and written), holding seminars and discussions. Banners and posters calling for rejection of all forms of corruption 'must' be put up in government offices as a media campaign about the dangers of corruption.